2019
DOI: 10.1111/scs.12782
|View full text |Cite
|
Sign up to set email alerts
|

Self‐care ability and sense of security among older persons when using an app as a tool for support

Abstract: The study’s rationale The need for home care among older persons is increasing, and mHealth is evolving to help meet the challenge. When developing an app to help maintain their health, it is essential to incorporate older persons’ preferences. Aims and objectives To describe and evaluate the experiences of self‐care support and sense of security among older persons using an interactive app to report health concerns. Methodological design and justification The study had a descriptive and evaluative design. Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 48 publications
(77 reference statements)
0
30
0
10
Order By: Relevance
“…13% (n = 11) of the studies reported interventions aimed at increasing the knowledge and self‐management skills of older people living with chronic diseases and thereby helping to decrease the use of health‐care resources and improve QoL among older people 70‐80 . Interventions offered comprised programs of symptom monitoring and testing devices for collecting and sending data to health‐care professionals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13% (n = 11) of the studies reported interventions aimed at increasing the knowledge and self‐management skills of older people living with chronic diseases and thereby helping to decrease the use of health‐care resources and improve QoL among older people 70‐80 . Interventions offered comprised programs of symptom monitoring and testing devices for collecting and sending data to health‐care professionals.…”
Section: Resultsmentioning
confidence: 99%
“…The channels used were videoconference 77,78,80 telephone 70,75 a digital health diary 73 apps with text 71 or message functions 74,79 . Some of the programs generated automatic feedback and risk assessment via algorithms, 71,72 whilst in others, data were audited directly by health care staff 70,77,79,80 …”
Section: Resultsmentioning
confidence: 99%
“…The procedure of the intervention has been described in detail elsewhere [25]. The older people were provided with a smartphone or tablet on which Interaktor had been installed.…”
Section: Methodsmentioning
confidence: 99%
“…1 ). A more detailed description of the recruitment process for the participants has been published elsewhere [ 24 , 25 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation